Desarrollo de un prototipo de un equipo Holter para la detección de arritmias cardíacas que permita correlacionar las señales ECG con las actividades diarias del paciente. (2023)
The analysis of the monitoring results of a Holter monitor is a task that involves a great effort on the part of the physician, since as a complement to the results provided by the Holter monitor, its results must be correlated with manual records, named patient diaries, which detail the activities performed by the patient during the test. With the purpose of identifying and evaluating to what degree an activity contributed to the generation of arrhythmia, confirming or discarding possible diagnoses and if applicable, starting the most ideal and immediately treatment. For this reason, this work seeks to support this process, creating an alternative to existing solutions, through the development of a prototype of a Holter device and an application for mobile devices that unifies both the Holter device information and patient information, allowing its correlation in an agile and easy way. Improving diagnosis times, while reducing potential human errors. For the management and execution of this work, the methodological initiative (CDIO) Conceive, Design, Implement and Operate is adopted, which allows the planning and execution of this work, focused on the achievement of the proposed objective, as well as its functional and technical validation. It is important to highlight the support of open source software tools in each of the stages, such as text editors, word processors, design platforms, libraries and development environment.